Chlorine Dioxide Inhibits African Swine Fever Virus by Blocking Viral Attachment and Destroying Viral Nucleic Acids and Proteins - Wei, Ruiping; Wang, Xiaoying; Liu, Xiaohong; Guo, Chunhe (Frontiers in Veterinary Science, 2022)
African swine fever (ASF) is a highly contagious disease and provokes severe economic losses and health threats. At present no effective vaccine or treatment is available to prevent or cure ASF. Consequently, there is an urgent need to develop effective drugs against ASF virus (ASFV). Chlorine dioxide (ClO2), an ideal biocide, has broad-spectrum antibacterial activity and no drug resistance. Here, we found that ClO2 strongly inhibited ASFV replication in porcine alveolar macrophages (PAMs). The inhibitory effect of ClO2 occurred during viral attachment rather than entry, indicating that ClO2 suppressed the early stage of virus life cycle. ClO2 showed a potent anti-ASFV effect when added either before, simultaneously with, or after virus infection. Furthermore, ClO2 could destroy viral nucleic acids and proteins, which may contribute to its capacity of inactivating ASFV virions. The minimum concentration of degradation of ASFV nucleic acids by ClO2 is 1.2 μg/mL, and the degradation is a temperature-dependent manner. These have guiding significance for ClO2 prevention and control of ASFV infection in pig farms. In addition, ClO2 decreased the expression of ASFV-induced inflammatory cytokines. Overall, our findings suggest that ClO2 may be an ideal candidate for the development of novel anti-ASFV prophylactic and therapeutic drugs in swine industry.